2018
DOI: 10.1002/qua.25620
|View full text |Cite
|
Sign up to set email alerts
|

Quantum information‐theoretic measures for the static screened Coulomb potential

Abstract: In this research work, the quantum information‐theoretic analysis of the static screened Coulomb potential has been carried out by studying both analytically and numerically the entropic measures, Fisher information as well as the Onicescu information energy of its wave function. Explicit expressions of these information‐theoretic measures were obtained. Using the Srivastava–Daoust linearization formula in terms of the multivariate Lauricella hypergeometric function, the Rényi entropy, Tsallis entropy, Onicesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 58 publications
1
28
0
Order By: Relevance
“…[16][17][18][19] Furthermore, these quantities provide different perspectives to statistic mechanics, [20][21][22][23][24][25][26] entropic uncertainty relations, [27][28][29] electron correlation, [30][31][32][33][34][35][36][37][38][39][40][41] orbital-free density functional theory (DFT), [42,43] and other applications. [44][45][46][47][48][49][50][51][52][53][54] In particular, by treating the electron density as a continuous probability distribution, these quantities are naturally extended to the position space and applied to numerous types of potential [55][56][57][58][59][60][61] and atomic and molecular systems. [30][31]…”
mentioning
confidence: 99%
“…[16][17][18][19] Furthermore, these quantities provide different perspectives to statistic mechanics, [20][21][22][23][24][25][26] entropic uncertainty relations, [27][28][29] electron correlation, [30][31][32][33][34][35][36][37][38][39][40][41] orbital-free density functional theory (DFT), [42,43] and other applications. [44][45][46][47][48][49][50][51][52][53][54] In particular, by treating the electron density as a continuous probability distribution, these quantities are naturally extended to the position space and applied to numerous types of potential [55][56][57][58][59][60][61] and atomic and molecular systems. [30][31]…”
mentioning
confidence: 99%
“…The momentum expectation value 〈 p 2 〉 is given by 〈〉p2=2πm20RitalicEnnormalℓ2()ritalicdr0π||Ynormalℓm(),θϕ2sinθitalicdθ,=12()2normalℓ+1||m〈〉r2, where 0π||Ynormalℓm(),θϕ2sinθitalicdθ=2normalℓ+14||m, and 〈〉r2=0RitalicEnnormalℓ2()ritalicdr, this after some algebraic manipulation yields 〈〉p2=V32μ()normalℓ+2n+141+22+8μV1normalℏ2+V22()n+normalℓ. …”
Section: Fisher Informationmentioning
confidence: 99%
“…Thus, several authors have reported the computation for Fisher information for different physical potential models. Among the works reported are: Fisher information and variance with Frost‐Musulin potential, Fisher information‐based uncertainty relation, Cramer‐Rao inequality and kinetic energy for the D‐dimensional central problem, information and complexity measures for the ring‐shaped modified Kratzer potential, Fisher information for position‐dependent mass Schrödinger system, quantum information‐theoretic measures for the static screened Coulomb potential, Fisher information of a single‐particle system with a central potential, Fisher information and complexity measure of generalized Morse potential model, Eigen solutions, Shannon entropy and Fisher information under Eckart Manning‐Rosen potential model, Eigensolution techniques, their applications and Fisher's information entropy of the Tietz‐Wei diatomic molecular model, Fisher information in confined hydrogen‐like ions, Fisher information in confined isotropic harmonic oscillator, Fisher information and complexity measure of Generalized Morse potential model, Shannon and Fisher entropy measures for a parity‐restricted harmonic oscillator, radial position‐momentum uncertainties for the infinite circular well and Fisher entropy, quantum information measures of infinite spherical well . In this study, the authors aimed at investigating the solutions of the radial Schrödinger equation and Fisher information confined in a potential family which is proposed in the course of this study.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Fisher information, being the sole component of the local measure, is primarily concerned with local changes that occur in probability density. [ 18–20 ] The study of Fisher information finds its significance in density functional. [ 21–23 ] Fisher information entropy, defined as probability density in position and momentum spaces, is expressed as follows [ 11,12 ] : Ir=[]ρ'()rfalse⇀2ρ()rfalse⇀dtruer=4ψ'truer2italicdr=4〈〉p22()2l+1||m〈〉r2 Ip=[]ρ'()pfalse⇀2ρ()pfalse⇀dtruep=4ψ'truep2italicdp=4〈〉r22()2l+1||m〈〉p2 …”
Section: Introductionmentioning
confidence: 99%
“…Generally, quantum information‐theoretic measures have been used to explore many areas of molecular, atomic, and reactive systems. [ 28–32 ] Recently, Isonguyo et al [ 20 ] , Yanez‐Navarro et al [ 33 ] and Pooja et al [ 34 ] studied the characteristic quantum information theory for screened Coulomb and Eckart potential models in one dimension, respectively. Many authors have investigated the quantum information for harmonic oscillators in one, two, and three dimensions [ 35,36 ] ; a single‐particle system with central potentials [ 11 ] ; and the shape and effect for quantum heterostructures, [ 37 ] pseudoharmonic potential, [ 38 ] hyperbolic well, [ 39 ] Tangent well, [ 40 ] Kratzer potential, [ 41 ] and many other potential models.…”
Section: Introductionmentioning
confidence: 99%